EDUCATION AND EARLY DETECTION AS A COMMUNITY DISCLOSURE EFFORT TO MENTAL HEALTH - Andikawati Fitriasari; Nunik Purwanti; Khamida; Nur Hidaayah (Community Service Journal of Indonesia, 2022)
Mental health is a problem that cannot be fully resolved, both at global and national levels. Public knowledge and understanding of mental health is an important point in realizing public openness to emotional mental disorders. The purpose of this activity is to increase knowledge about mental health and to detect cases of mental emotional disorders in the community early. The method used in this community service activity is providing health education. This activity was carried out for one month and was attended by 70 cadres. Knowledge of mental health and early detection of mental emotional disorders using the Self Rating Questionnaire). The results of community service show that knowledge about mental health is very good and mental emotional disorders are detected.